1957
DOI: 10.6028/jres.059.013
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical studies of the destructive alkali-aggregate reaction in concrete

Abstract: In a further stud.I' of t he a lka li-aggregate reaction in high-alkali cements, 11 reactiv e a nd nonreactive experimental aggregates were examined by several procedures. On comparing t he results of each m ethod with th e standard expansion-bar test, it appears that eac h property studied has some bearing on the expansion characteristics of each aggregate. For exa,mple: (1) The chemical durabili ty as determined by the interferometer procedure was poor for t he aggregates t hat showed excessive expansion, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Soaking the slides in dry acetone prior to attaching PEG-silane was crucial to remove any water molecules adsorbed at the glass/air interface due to the hygroscopic nature of glass surfaces. 33 Given our extremely dry winter conditions, we had observed better surfaces in the winter season, which made us realize how critical this step is. Any residual water would elicit the premature hydrolysis of the PEG-Si(OEt) 3 (eq 2).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Soaking the slides in dry acetone prior to attaching PEG-silane was crucial to remove any water molecules adsorbed at the glass/air interface due to the hygroscopic nature of glass surfaces. 33 Given our extremely dry winter conditions, we had observed better surfaces in the winter season, which made us realize how critical this step is. Any residual water would elicit the premature hydrolysis of the PEG-Si(OEt) 3 (eq 2).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…To clean the coverslip and also maximize the number of silanol groups exposed, we performed a piranha solution cleaning (90 min) followed by a mild etching using NaOH (0.5 M for 30 min). Soaking the slides in dry acetone prior to attaching PEG-silane was crucial to remove any water molecules adsorbed at the glass/air interface due to the hygroscopic nature of glass surfaces . Given our extremely dry winter conditions, we had observed better surfaces in the winter season, which made us realize how critical this step is.…”
Section: Resultsmentioning
confidence: 99%
“…There is no doubt that the higher the specific surface area of the glass powder, the greater its pozzolanic activity. An analysis of scientific studies has also shown that the addition of finely ground glass powder with a specific surface area of 0-0.079 mm causes, similar to the addition of slag, fly ash, or silica fume [71], a reduction in the shrinkage of mortars and concretes compared to reference samples without additives. The indicated specific surface area of the powder also limits material destruction in cases where the sample contains reactive aggregates.…”
Section: Waste Glassmentioning
confidence: 99%
“…In the sixties, many studies were devoted to the use of crushed glass waste as an aggregate for concrete production [4][5][6]. This aggregate was also applied in road construction.…”
Section: Introductionmentioning
confidence: 99%